Sexual size dimorphism in calanoid copepods (Centropagidae) from Patagonia (Argentina) - García, Roberto Daniel (2013)
Calanoid copepods of the genus Boeckella and Parabroteas (P. sarsi) are dominant in zooplankton communities of Patagonian lakes and ponds. This study addresses the occurrence of sexual size dimorphism in calanoid copepods of the genus Boeckella and in the monospecific genus Parabroteas occurring in 12 lakes and ponds of Patagonia (Argentina). The morphometric analysis performed showed that in all the species studied the female is larger than the male, although the difference in size among sexes was found to be variable between species. Interestingly, all species showed significant intraspecific stability in their sexual size dimorphism despite potential differences in their environments regarding predation pressure, environmental stability (permanent or temporary waters) and altitude distribution of populations. Finally, we discuss the potential implications of sexual dimorphism in terms of resource use and vulnerability to predation among other environmental forces which may play a role in promoting larger female to male size.